1998
DOI: 10.1136/hrt.79.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Is metabolic syndrome a discrete entity in the general population? Evidence from the Caerphilly and Speedwell population studies

Abstract: Objective-To examine the clinical and epidemiological utility of the concepts of metabolic syndrome and insulin resistance syndrome in two prospective cohort studies of white men. Methods-Men aged 45-63 years were screened for evidence of ischaemic heart disease (IHD) between 1979 and 1982 and followed up at regular intervals thereafter. Non-fatal coronary events were validated from hospital records and fatal coronary events from death certificates. Results-Analysis of serum insulin concentrations in non-diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 35 publications
0
38
0
1
Order By: Relevance
“…Full details of all laboratory methods used for determination of fasting insulin, glucose and lipid parameters have been reported in detail elsewhere. 14 …”
Section: Study Population and Survey Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full details of all laboratory methods used for determination of fasting insulin, glucose and lipid parameters have been reported in detail elsewhere. 14 …”
Section: Study Population and Survey Methodsmentioning
confidence: 99%
“…Survey methods have been described in detail previously. 13,14 Laboratory methods All blood samples were taken with minimum haemostasis after an overnight fast. Full details of all laboratory methods used for determination of fasting insulin, glucose and lipid parameters have been reported in detail elsewhere.…”
Section: Study Population and Survey Methodsmentioning
confidence: 99%
“…Individuals with any four-, five-, or six-component groupings had no greater excess IMT than the sum of the same factors taken separately. The cross-sectional studies by Alexander et al (44) and Yarnell et al (101) showed that the impact of the syndrome on CVD was greatly attenuated in a multivariate analysis by controlling for certain of its components, thereby suggesting that the whole is not greater than its parts. Also, in a prospective study of diabetic and nondiabetic subjects free of CVD and followed for an average of 11 years, the risk of incident CHD associated with the syndrome was no greater than that explained by the presence of its components (34).…”
Section: Diabetes Care 28:2289 -2304 2005mentioning
confidence: 99%
“…13 Some investigators have even questioned the existence of a distinct IRS. 14 There is some evidence from cell biology and experimental research supporting the direct effect of insulin on atherosclerosis, 7 but the current balance of evidence gives more support to the view that the association of hyperinsulinemia with atherosclerotic vascular diseases is mediated through the clustering of other cardiovascular risk factors with hyperinsulinemia and the underlying insulin resistance. 8,15 In the 22-year follow-up of the Helsinki Policemen Study, 2 hyperinsulinemia was found to predict the risk of CHD independently of other risk factors, whereas the positive association between hyperinsulinemia and the risk of stroke became nonsignificant after adjustment for other risk factors.…”
mentioning
confidence: 99%